2017
DOI: 10.6061/clinics/2017(01)04
|View full text |Cite
|
Sign up to set email alerts
|

Late preterm infants' motor development until term age

Abstract: OBJECTIVES:To analyze the motor development of late preterm newborn infants (LPI) from birth to term-corrected age using the Test of Infant Motor Performance (TIMP) and to compare the obtained results with those of term infants at birth.METHODS:Prospective cohort study, 29 late preterm newborn infants were evaluated by the TIMP at birth and every two weeks until term-corrected age. The TIMP was administered to 88 term infants at birth.RESULTS:The mean TIMP score of late preterm newborn infants was 51.9±5.8 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…These findings were comparable to those reported by in an Indian tertiary care teaching hospital [31]. Also, LPT neonates had significantly lower birth weight and head circumference, which agrees with some earlier reports [12,32]. Accordingly, the incidence of 11.4% of SGA was significantly higher in LPT neonates compared with the FT group; this was comparable to the results of Araújo et al [33] as about one quarter of the LPT neonates in their study were SGA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings were comparable to those reported by in an Indian tertiary care teaching hospital [31]. Also, LPT neonates had significantly lower birth weight and head circumference, which agrees with some earlier reports [12,32]. Accordingly, the incidence of 11.4% of SGA was significantly higher in LPT neonates compared with the FT group; this was comparable to the results of Araújo et al [33] as about one quarter of the LPT neonates in their study were SGA.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, cortical volume increases by 50% during this time. Therefore, the occurrence of brain injury during this critical period of neural development might affect late cerebral development [12].…”
Section: Introductionmentioning
confidence: 99%
“…[14] Evaluating the newborns birth weight in our study showed that there was a significant progressive increase in the mean birth weight with increasing the GA this finding was similar to what reported by Santos (Santos et al, 2017). [15] Mean birth weight s significantly higher in FT. Betul et al, (2018) also concluded that all measurements of late preterm infants were smaller than those of term infants. [16] In our study, the LP infants had a higher incidence of formula feeding compared with full term infants, bottle feeding was significantly higher in LP infants group which is similar to the results of other studies.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, these authors added that motor skills at the beginning of the Early Childhood Education (ECE) stage present similar levels with respect to those students who were born prematurely. Also, Santos et al [ 18 ] found that healthy premature infants do not experience profound delays in motor competence.…”
Section: Introductionmentioning
confidence: 99%